(untitled) (Scientia Agropecuaria, 2021)
Azotobacter is a type of bacterium nonpathogenic, Gram-negative with ability to synthesize simultaneously under aerobic conditions two biodegradable polymers extra and intracellular such as alginate and polyhydroxyalkanoates, respectively, whose physical, mechanical, and biodegradable properties have awoken the interest in the industry. Thus, this review compiles information on synthesis chemistry of these polymers and the genetic modification of this bacterium in order to produce a particular polymer and improve its yields. Additionally, we show that alginates obtained present a higher molecular weight, degree of acetylation and M/G ratio compared with other organic sources like seaweed; while polyhydroxyalkanoate polymers have better physical and mechanical characteristics (melting temperature, Young’s modulus, elongation and glass transition temperature) compared with other synthetic polymers. These characteristics present in both polymers have allowed the development of several applications in the food, pharmaceutical, medical and agronomic industries. Finally, it is necessary to study new strategies to control the variability of the degree of acetylation and molecular weight for alginate polymers and improve the production of polyhydroxyalkanoates in order to propose new future applications in the industry.